Dual antiretroviral therapy for HIV infection. Issue 8 (3rd August 2017) - Soriano, Vicente; Fernandez-Montero, Jose Vicente; Benitez-Gutierrez, Laura; Mendoza, Carmen de; Arias, Ana; Barreiro, Pablo; Peña, José M.; Labarga, Pablo
ABSTRACT: Introduction : For two decades, triple combinations of antiretrovirals have been the standard treatment for HIV infection. The challenges of such lifelong therapy include long-term side effects, high costs and reduced drug adherence. The recent advent of more potent and safer antiretrovirals has renewed the interest for simpler HIV regimens. Areas covered : We discuss the pros and cons of dual antiretroviral therapies in both drug-naïve and in treatment-experienced patients with viral suppression (switch strategy). Expert opinion : Some dual antiretroviral regimens are safe and efficacious, particularly as maintenance therapy. At this time, combinations of dolutegravir plus rilpivirine represent the best dual regimen. Longer follow-up and larger study populations are needed before supporting dolutegravir plus lamivudine. In contrast, dual therapy based on maraviroc is less effective. Although dual regimens with boosted protease inhibitors plus either lamivudine or raltegravir may be effective, they are penalized by metabolic side effects and risk for drug interactions. The newest dual regimens could save money, reduce toxicity and spare drug options for the future. For the first time in HIV therapeutics, less can be more. Dual therapy switching has set up a new paradigm in HIV treatment that uses induction-maintenance.